Locus coeruleus tyrosine hydroxylase positive neurons mediated the peripheral and central therapeutic effects of transcutaneous auricular vagus nerve stimulation (taVNS) in MRL/lpr mice - Hongjie Lv; Xiu Yu; Ping Wang; Mengxian Luo; Yijun Luo; Haimei Lu; Keer Wang; Anran Xi; Chengping Wen; Zhenghao Xu (Brain Stimulation, 2024)
Objective: This study aims to investigate the effects of transcutaneous auricular vagus nerve stimulation (taVNS) on the development of systemic lupus erythematosus (SLE) in MRL/lpr mice. Methods: MRL/lpr mice were treated with taVNS for ten weeks. Locus coeruleus (LC) tyrosine hydroxylase positive (TH+) neurons were selectively lesioned by stereotactic injection of 6-hydroxydopamine (6-OHDA) or selectively activated by chemogenetic methods. Sympathetic denervation was conducted by intraperitoneal injection of 6-OHDA. Results: TaVNS activated the TH + neurons in LC. TaVNS produced central therapeutic effects by reducing the number of hippocampal microglia, and increasing the number of surviving LC TH+ neurons in MRL/lpr mice. TaVNS also retarded the development of lymphadenectasis and splenomegaly, decreased the proportion of double-negative T (DNT) cells, and alleviated nephritis in MRL/lpr mice. The lesion of LC TH+ neurons eliminated both these central and peripheral therapeutic effects of taVNS, while chemogenetic activation of LC TH+ neurons mimicked most central and peripheral protective effects of taVNS in MRL/lpr mice. Furthermore, taVNS regulated the autonomic nervous system in MRL/lpr mice. Conclusion: This study provides direct evidence that taVNS can retard the development of peripheral and central symptoms of SLE, which is mediated by the LC TH+ neurons.